ASSESSMENT OF TOPICAL ANTIMICROBIAL POTENCY OF SARGASSUM SP. EXTRACT - Mauly, Nur Maydiana; Stefani, Zalsa Riski; Ramadhani, Amandha Gusti; Ramadhan, Muhammad Raffid; Rahman, Rahma Aulia; Darmawan, Noval Ramadhani; Lestari, Pingky; Rafiqi, Muhammad Aufa; Saputra, Rizqy Hadi; Amiin, Muhammad Kholiqul (University of Lampung, 2024)
Sargassum is a macroalgae in tropical and subtropical waters. Sargassum sp. contains Mg, Na, Fe, tannin, iodine, and phenol. This study aims to determine the antibacterial potential of Sargassum sp. extract in inhibiting the growth of Staphylococcus aureus. Samples were dried in the sun and then pureed using a blender and extracted by maceration method, for 7 days with methanol solvent at a ratio of 1: 3, evaporated using a rotary vacuum evaporator and water bath to get extract results. Antibacterial activity was tested using the disc diffusion method against various concentrations of extracts, namely 10,000, 5000, 1000, 100, 10, and the control. The results showed that this study implies that Sargassum sp. extract has potential as a natural antibacterial against Staphylococcus aureus. Still, its effectiveness is determined by the extraction method and concentration used.